Deixis Analysis of The Novel The Twelfth Card (2005) - Nugraha, Dian Setya, Dra. Malikatul Laila, M. Hum, Siti Fatimah, S. Pd, M. Hum (2015)
The objectives of the study are to find out the forms, and clarify the meaning of deixis used in The Twelfth Card novel. In collecting the data, the writer uses observation and documentation method by selecting the deixis forms that can be found in The Twelfth Card novel. The sources of data are The Twelfth Card novel. This research employs the theory of deixis in discourse analysis, and theory of context to clarify the reference and meanings of deixis. The result of the study shows that, there are 2686 deixis divided into five types. (1) person deixis are 2222 or 83% that is divided into first person deixis consisting of 466 deixis or 20, 97 %, second person deixis consisting of 335 deixis or 15,08 %, and third person deixis consisting of 1421 deixis or 63,95 %. (2) Place deixis consists of 149 deixis or 5%. (3) Time deixis consists of 176 deixis or 7%. (4) Discourse deixis consists 116 deixis or 4 %. (5) Social deixis consists of 21 deixis or 1%. Social deixis is divided into absolute social deixis (15 items / 71, 43% of total social deixis) and relational social deixis (6 items or 28,57% of total social deixis). The reference and meaning of deixis the researcher analyzed are ten references. (1) Based on first person deixis, the most dominant reference is Geneva Settle that appears 123 times or 34,45 %. (2) Based on second person deixis, the most dominant reference is Geneva Settle that appears 71 times or 24,91 %. (3) Based on third person deixis, the most dominant reference is also Geneva Settle that appears 299 times or 23,67 %. (4) Based on the proximal place deixis, the most dominant reference is Lincoln Rhyme's Office; it appears 36 times or 24, 16%. (5) Based on the distal place deixis, the most dominant reference is Library of African-American Museum that appears 54 times or 36, 24%. (6) Based on the past time deixis, the most dominant reference is Tuesday morning that appears 12 times or 7, 03 %. (7) Based on the present time deixis, the most dominant reference is the time when the main characters gathering in the Rhyme's Office, the deixis appears 30 times or 16,85 %.(8) Based on the future time deixis, the most dominant reference is Tuesday morning; it appears 39 times or 18,9 %. (9) Based on the portion of discourse, the most dominant reference is the situation where Geneva Settle was attacked by Thompson Boyd that appears 41 times or 41, 03 %. (10) Based on the social relationship between the speakers and the addressee, the most dominant reference is Lincoln Rhyme who has a position as the leader of Investigation Team of Geneva Settle case; this reference appears 8 times or 34,78 %.